2019
DOI: 10.1039/c9ra01804b
|View full text |Cite
|
Sign up to set email alerts
|

Silver derivatives of multi-donor heterocyclic thioamides as antimicrobial/anticancer agents: unusual bio-activity against methicillin resistantS. aureus,S. epidermidis, andE. faecalisand human bone cancerMG63cell line

Abstract: A series of biosafe mixed-ligand complexes of silver with heterocyclic thioamides have been studied for their antimicrobial/anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Given the traditional antimicrobial properties shown by silver(I) complexes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the activity of silver(I) complexes Ag1 – 3 and the ligands, tia and 1,8-naph used for their synthesis, was determined against two Gram-positive ( S . aureus and L. monocytogenes ), two Gram-negative ( E. coli and P. aeruginosa ATCC 10332 and BK25H [ 50 ]) bacteria, and three Candida species ( C. albicans , C. krusei, and C. parapsilosis ; Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the traditional antimicrobial properties shown by silver(I) complexes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], the activity of silver(I) complexes Ag1 – 3 and the ligands, tia and 1,8-naph used for their synthesis, was determined against two Gram-positive ( S . aureus and L. monocytogenes ), two Gram-negative ( E. coli and P. aeruginosa ATCC 10332 and BK25H [ 50 ]) bacteria, and three Candida species ( C. albicans , C. krusei, and C. parapsilosis ; Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The significant antimicrobial activity has also been manifested by silver(I) complexes with N -methylbenzothiazole-2-thione (mbtt), [(mbtt) 2 Ag( μ -mbtt) 2 Ag(mbtt) 2 ](NO 3 ) 2 and [Ag(mbtt) 3 ]CF 3 SO 3 against certain Gram-negative ( Xanthomonas campestris , Escherichia coli ) and Gram-positive ( Bacillus subtilis , Bacillus cereus , Staphylococcus aureus ) bacteria [ 32 ]. Similarly, silver(I) complexes with N -substituted imidazolidine-2-thiones, purine-6-thione, 2-thiouracil, pyrimidine-2-thione, and pyridine-2-thione have shown moderate to good antimicrobial activity against Gram-positive (methicillin-resistant Staphylococcus aureus MRSA and Staphylococcus aureus ), and Gram-negative ( Staphylococcus epidermidis , Enterococcus faecalis , Shigella flexneri ) bacteria and a yeast Candida albicans [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that for a high antibacterial activity of a compound, an appropriate lipophilicity/hydrophilicity balance is also crucial, as it defines the binding and subsequent internalization of the compound to the bacterial cell. 42 Therefore, the increased lipophilic character of 5, together with its low potential for the development of favorable intermolecular interactions, is detrimental for its antibacterial activity. Moreover, 5 provides an example of a compound for which the presence of CF 3 -substitution is not beneficial for its bioactivity, in contrast to what has been claimed for many CF 3 -substituted compounds in the literature, 66,67 rendering its influence controversial indeed.…”
Section: Papermentioning
confidence: 99%
“…In the presence of a high concentration of Cl − ions, degradation of the Ag( i ) complexes might take place, by precipitation of Ag( i ) ions in the form of highly insoluble AgCl, therefore lowering their potential bioactivity and preventing them from reaching the target sites. 12 Another complication might result from the soft Lewis acid character of Ag( i ) ions and their high propensity to associate strongly with soft Lewis bases. As a consequence, coordinatively unsaturated Ag( i ) complexes can interact with S-donors in S-containing proteins that exist in our body, resulting in their immobilization and, therefore, not allowing them to perform their cytotoxic function.…”
Section: Introductionmentioning
confidence: 99%